Spatial Structure of Modern Moscow - D. V. Goloukhova (Vestnik MGIMO-Universiteta)
The article is focused on the spatial structure of modern Moscow and features distinguishing it from the cities of Western Europe and the US. The city has hybrid spatial structure combining elements which emerged on different stages of the city development. In the 14th century two tendencies appeared: the prestige of the city centre and opposition of Western districts as more prestigious to Eastern districts as less prestigious. Crucial spatial characteristics emerged in the Soviet era and up to now they define the image of Moscow. Firstly, it's a peculiar density profile. Population density in post-socialist cities tends to increase as we move further from the city centre while in Western European cities population density is the highest in central districts. Secondly, elementary units of Moscow spatial structure are so called micro-districts (neighbourhoods). The concept of a microdistrict was very popular with Soviet urban planners and widely applied in the residential construction. Another peculiarity of Moscow spatial structure is social heterogeneity of districts and absence of ethnic quarters or ghettos. Furthermore, significant part of the city area is occupied by former industrials zones which are not used anymore and need to be reconstructed. With transition to market economy a number of spatial changes emerged. They were partly related to the large-scale privatization, infill construction and lack of effective urban planning policy. In conclusion the article states the need for the new model of spatial organization which would take into account the specifics of Russian reality.